Plan de gestión para la puesta en marcha de un hotel categoría tres estrellas en la zona de San Vito de Coto Brus utilizando la metodología PRINCE2® - Purcallas-Mesa, Patricia; Rojas-Gilardi, Norberto (Instituto Tecnológico de Costa Rica, 2011)
Due to multiple factors, Coto Brus County has been classified as one of the poorest counties in Costa Rica, although it has a great potential to act towards the natural resources of the area. Considering this, there is an opportunity to develop a three stars hotel focused in eco-friendly tourism. This will have a positive impact in the population and will certainly generate earnings for the investors. In order to achieve all the desired benefits in the project of the three star hotel in San Vito de Coto Brus, it is necessary to develop a plan for the implementation that guarantees the fulfillment of all the needs and expectations of the developers. Thus, the general objective of this project is to develop a plan for the implementation of a three star hotel, located in San Vito de Coto Brus, using the PRINCE2® project management methodology. In addition, the following specific objectives were set up:  Establish the prerequisites in order to decide if the project is worthwhile and if it has a solid rationale.  Set the solid foundations for the project plan, taking into account all the work that must be done to deliver the project.  Establish the product delivery plan and the acceptance criteria, so that the outcome of every project stage is successful.  Establish the closure plan to provide a fixed point at which acceptance for the project products is confirmed. This is a descriptive investigation, based on primary and secondary sources. Subjects, main activities and tools to gather information where defined in order to accomplish every specific objective As one of the main conclusions, the PRINCE2® is a process-based structured project management methodology focused on product delivery. The project plan includes all the key elements to ensure that the expectations and client requirements are fulfilled. As a recommendation, project management according to PRINCE2® must be tailored to project factors and the complexity of its processes, in order to avoid becoming a template-driven project. The final recommendation is that all the information regarding to the current legislation, costs, schedule, project products, strategies, tolerances, and exceptions, must be updated at the stage of project launching.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Área Académica Gerencia de Proyectos, 2011.
Keywords: Gestión de riesgos; Comunicaciones; Diseño; Construcción; Costos